Torsional vibration model based optimization of gearbox geometric design parameters to reduce rattle noise in an automotive transmission - Bozca, Mehmet (PERGAMON-ELSEVIER SCIENCE LTD, 2010)
The optimization of gearbox geometric design parameters to reduce rattle noise in an automotive transmission based on a torsional vibration model approach is studied. Rattle noise is calculated and simulated based on the design parameters of a 5-speed gearbox, and all pinion gears and wheel gears are helical. The effect of the design parameters on rattle noise is analyzed. The observed rattle noise profiles are obtained depending on the design parameters. During the optimization, a four-degree-of-freedom torsional vibration model of the pinion gear-wheel gear system is obtained and the minimum singular value of the transfer matrix is considered as the objective functions and design parameters are optimized under several constraints that include bending stress, contact stress and a constant distance between gear centers. Therefore, by optimizing the geometric parameters of the gearbox such as, the module, number of teeth, axial clearance, and backlash, it is possible to obtain a light-weight-gearbox structure and minimize the rattling noise. It is concluded that the optimized geometric design parameters lower the rattle noise by 10% compared to the calculated rattle noise for sample gearbox. All optimized geometric design parameters also satisfy all constraints. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Optimization; Gearbox; Rattle noise; Torsional vibration; Automotive transmission; FATIGUE; TOOTH; Engineering